The Role of Institutional Uncertainty for Social Sustainability of Companies and Supply Chains - Nikolas K. Kelling; Philipp C. Sauer; Stefan Gold; Stefan Seuring (Journal of Business Ethics, 2020)
Global sourcing largely occurs from so-called emerging markets and developing economies (EMDEs). In these contexts, substantial leverage effects for sustainability in supply chains (SCs) can be expected by reducing adverse impacts on society and minimising related risks. For this ethical end, an adequate understanding of the respective sourcing contexts is fundamental. This case study of South Africa's (SA) mining sector uses institutional theory and the notion of institutional uncertainty to empirically analyse the challenges associated with establishing social sustainability. The case study research is informed by 39 semi-structured interviews with top management representatives and various state and non-state decision makers in SA. Our findings suggest that (social) sustainability in the institutional field is mainly shaped by the Social and Labour Plan institution, induced by state actors and mining companies' practices. However, four weakening factors were identified that adversely affect this regulative institution, drive institutional uncertainty and allow for mining companies' gradual decoupling. Contrastingly, complementing pressures of non-state actors limit institutional uncertainty and push toward mainstreaming the stipulations of the institution. This study contributes to the business ethics literature by providing an in-depth exploration of institutional uncertainty's drivers and barriers within an upstream SC setting and shedding light on multiple actors' interplay and relevance in sector-wide sustainability. The findings are condensed into three main propositions as well as an analytical framework as a basis for follow-up research. This case study helps practitioners understand and manage complexity that results from actor plurality and institutional uncertainty in EMDEs.
Keywords: 300; Institutional uncertainty; Decoupling; Compliance; Social sustainability; Mineral resources